Rancang Bangun Alat Monitoring Penyiraman Tanaman Otomatis Dengan NodeMcu Berbasis Internet Of Things (IoT) - Dody Banjarnahor; Moranain Mungkin; Muhammad Fadlan Siregar (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2022)
In today's modern era, the use of the internet of things (IoT) has been widely applied in various fields, almost all electronic devices are connected to the internet. Along with the development of technology, the application of this technology in the field of agriculture really needs to be considered. Due to the increasing need for plant monitoring and care. Therefore, the importance of plant care and monitoring so that plants can produce good quality. In this research, an automatic plant watering system is designed that is connected to the internet network so that users can monitor plants so that they are maintained and produce plant quality. This system is designed using a NodeMcu microcontroller as the center of the system and as a data sender between systems and a web server. In this research, a monitoring system and automatic plant watering has been successful by reading the size of the moisture in the soil. The result is this system can provide water needs for plants. Then the system sends information to the website page that has been built so that users can monitor their plants anytime and anywhere.